2021
DOI: 10.1038/s41598-021-97586-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the fecal microbiome and antimicrobial resistome in commercial piglets during the weaning period

Abstract: This study aimed to characterize the alteration of the fecal microbiome and antimicrobial resistance (AMR) determinants in 24 piglets at day 3 pre-weaning (D. − 3), weaning day (D.0), days 3 (D.3) and 8 post-weaning (D.8), using whole-genome shotgun sequencing. Distinct clusters of microbiomes and AMR determinants were observed at D.8 when Prevotella (20.9%) was the major genus, whereas at D. − 3–D.3, Alistipes (6.9–12.7%) and Bacteroides (5.2–8.5%) were the major genera. Lactobacillus and Escherichia were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 75 publications
5
6
0
Order By: Relevance
“…The dramatic impact of weaning on the swine microbiome has been previously reported, and our results confirm that microbiome richness and diversity increase significantly post-weaning [57][58][59][60][61]. As with previous reports, we found that Bacteroides were predominant in the samples taken just prior to weaning [61,62]. Using DMM enterotyping, we observed that pre-weaning samples were also characterized by a relative dominance of Alistipes, Cloacibacillus, Escherichia, and Intestinimonas.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The dramatic impact of weaning on the swine microbiome has been previously reported, and our results confirm that microbiome richness and diversity increase significantly post-weaning [57][58][59][60][61]. As with previous reports, we found that Bacteroides were predominant in the samples taken just prior to weaning [61,62]. Using DMM enterotyping, we observed that pre-weaning samples were also characterized by a relative dominance of Alistipes, Cloacibacillus, Escherichia, and Intestinimonas.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, these four genera did not reach the top 10 most prevalent genera in any of the post-weaning samples, suggesting that their relative abundance within the pre-weaning samples is a defining characteristic of the suckling piglet fecal microbiome. Previous studies of the peri-weaning microbiome also found a predominance of Alistipes [ 62 ].…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have shown that tetracyclines and MLSs are the most common antibiotic resistance classes in weaned pigs receiving or not receiving in-feed antibiotics, and the findings of the current study are consistent with this [8,47]. High levels of beta-lactam resistance also were found in both the negative control and the antibiotic groups.…”
Section: Plos Onesupporting
confidence: 90%
“…These genera are regarded as being beneficial microbes due to a variety of characteristics, including the ability to produce antibacterial substances (e.g., bacteriocins, organic acids) that inhibit growth of pathogens, the ability to increase carbohydrate metabolism by utilizing dietary starch and fiber, and the ability to produce short-chain fatty acids (SCFAs) that reduce gut inflammation [2,7,13,40,[43][44][45][46]. The group receiving chlortetracycline showed an increase in Proteobacteria and Bacteroidetes, which is consistent with prior research demonstrating that antibiotic administration could boost these phyla [6][7][8]47]. However, several studies have suggested that enhanced numbers of Bacteroidetes may promote host health by enhancing nutrient digestion and absorption [2,7].…”
Section: Plos Onesupporting
confidence: 83%
See 1 more Smart Citation